PENINGKATAN PENGETAHUAN TENTANG DEMENSIA MELALUI PENYULUHAN WARGA DI KELURAHAN TOMANG JAKARTA BARAT - Sidarta, Nuryani (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2025)
Dementia is a condition that mainly affects the elderly. Dementia not only causes disability, but also reduces the sufferer’s quality of life. However, recent studies predict an increase in the prevalence of dementia by almost triple by 2050 compared to 2019. Therefore, various preventive efforts need to be taken. This community service activity aims to socialize physical exercise as one of the preventive efforts that is easy and inexpensive, but has proven to help prevent dementia. Counseling on how to do physical exercise properly was carried out by involving 35 residents, both adult men and women aged 18 – 50 years old.. The participants were selected based on their physical abilities and ability to train their families in the residencies. Not only was the material presentation, but a physical exercise demonstration was also accompanied by this counseling. In this community service, pre-test and post-test scores were also taken from the participants. From this assessment, it was found that the participants’ knowledge increased by 16.11%.